1996
DOI: 10.1002/chem.19960021222
|View full text |Cite
|
Sign up to set email alerts
|

Heterocyclic Carbenes: A High‐Yielding Synthesis of Novel, Functionalized N‐Heterocyclic Carbenes in Liquid Ammonia

Abstract: To date the only free carbenes of the imidazoline-2-ylidene type to have been described in the literature are those bearing simple hydrocarbon or haloalkyl and -aryl substituents. We report here a novel, versatile and high-yielding method for the synthesis of N-heterocyclic carbenes in a mixture of liquid ammonia and aprotic organic solvents. Deprotonation of the imidazolium precursor salts proceeds under mild conditions within a few minutes at temperatures below -30 "C, and side reactions are thus avoided. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
204
0
19

Year Published

1998
1998
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 354 publications
(231 citation statements)
references
References 64 publications
8
204
0
19
Order By: Relevance
“…(121) 1,3-Dicyclohexylimidazolium chloride was synthesized according to a procedure reported in literature. [169] A 500 ml three-necked flask was equipped with an interior thermometer and a dropping funnel. To a solution of freshly distilled cyclohexylamine (11.4 ml, 9.92 g, 100 mmol) in toluene (100 ml), solid paraformaldehyde was added , 11.5 ml, 5.80 g glyoxal, 100 mmol) was slowly added via another dropping funnel.…”
Section: Synthesis Of Tetra-nhc Complexes For Reference Purposesmentioning
confidence: 99%
“…(121) 1,3-Dicyclohexylimidazolium chloride was synthesized according to a procedure reported in literature. [169] A 500 ml three-necked flask was equipped with an interior thermometer and a dropping funnel. To a solution of freshly distilled cyclohexylamine (11.4 ml, 9.92 g, 100 mmol) in toluene (100 ml), solid paraformaldehyde was added , 11.5 ml, 5.80 g glyoxal, 100 mmol) was slowly added via another dropping funnel.…”
Section: Synthesis Of Tetra-nhc Complexes For Reference Purposesmentioning
confidence: 99%
“…Mössbauer spectroscopy and X-ray crystallographic studies of the compound, [ 3 ], have recently been carried out at various temperatures 1,2 . The X-ray study revealed that a temperature dependent electron transfer takes place between only two of the three Fe-atoms at temperatures higher than 35 K. Below this temperature the valence of all three Fe-atoms is trapped.…”
Section: Bothmentioning
confidence: 99%
“…In the commonly used method in the synthesis of Ag(I)-NHC complexes, a silver base has been used as agent of deprotonation. In this context silver bases (Ag 2 O, AgOAc, and Ag 2 CO 3 ) and the solvents (1,2-dichloroethane, acetone, acetonitrile, DMF, DMSO and methanol) have been used [27][28][29][30]. Ruthenium complexes, recently playing an influential role in a variety of studies on catalytic processes have made a great progress.…”
Section: Introductionmentioning
confidence: 99%